A Defense and Definition of Construct Validity in Psychology. Issue 4 (December 2019) - Stone, Caroline
Abstract : Psychologists say a measure has construct validity when it, in fact, measures the construct it is intended to measure. Construct validity is both an important notion in psychological research methods and the source of much confusion and debate among psychologists. I argue that this confusion arises, in part, because of a failure to distinguish between construct validity, a feature of measures relative to a construct, and construct legitimacy, a feature of the construct itself. I propose a prescriptive account of construct validity on the basis of this distinction, then provide evidence for my account through two examples from research psychology.